2020
DOI: 10.1177/0963662520950671
|View full text |Cite
|
Sign up to set email alerts
|

Exploring scholars’ public engagement goals in Canada and the United States

Abstract: We have little systematic knowledge about scholars’ goals for public engagement in the academic literature. This study therefore provides a secondary analysis of two surveys of scholars that included closed-ended questions about goals. One survey from 2017 was from a sample of Canadian grant recipients from a federal science funding agency, while the second survey from 2018 comes from a sample of professors at top American research universities. The focus of this research is on both presenting novel data about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 19 publications
0
43
0
1
Order By: Relevance
“…More recent efforts turned to improving the quality of risk communication, often through in-person training (Besley, Dudo, Yuan, & AbiGhannam, 2016;Miller, Fahy, & Team, 2009;Rodgers et al, 2018) and developing evidence-based guidance materials (e.g., Baron, 2010;Fischhoff et al, 2011). One aspect of improving the quality of risk communication revolved around helping trainers and messengers move beyond simply discussing communication tactics (e.g., speaking clearly, telling stories, considering nonverbal cues), to thinking more about effectiveness, including carefully selecting objectives beyond conveying scientific knowledge (e.g., fostering trustworthiness or beliefs) and clarifying overall goals (e.g., behavior change, enhancing legitimacy, or learning from stakeholders) (Besley, Newman, Dudo, & Tiffany, 2020;Brewer, 2011;, as well as structural and procedural organizational changes like making risk communication evaluations a standard operating procedure (Fischhoff, 2019).…”
Section: Messengersmentioning
confidence: 99%
“…More recent efforts turned to improving the quality of risk communication, often through in-person training (Besley, Dudo, Yuan, & AbiGhannam, 2016;Miller, Fahy, & Team, 2009;Rodgers et al, 2018) and developing evidence-based guidance materials (e.g., Baron, 2010;Fischhoff et al, 2011). One aspect of improving the quality of risk communication revolved around helping trainers and messengers move beyond simply discussing communication tactics (e.g., speaking clearly, telling stories, considering nonverbal cues), to thinking more about effectiveness, including carefully selecting objectives beyond conveying scientific knowledge (e.g., fostering trustworthiness or beliefs) and clarifying overall goals (e.g., behavior change, enhancing legitimacy, or learning from stakeholders) (Besley, Newman, Dudo, & Tiffany, 2020;Brewer, 2011;, as well as structural and procedural organizational changes like making risk communication evaluations a standard operating procedure (Fischhoff, 2019).…”
Section: Messengersmentioning
confidence: 99%
“…In the current more networked and digitalised science communication landscape, scientists may play different roles in the interactions with wider audiences online. Recently, Besley, Newman et al [2020] described six contributions or foci that scientists have with science communication activities, which were ensuring that policymakers use scientific evidence, society values science, adequate funding for scientific research is obtained, helping citizens make better life decisions based on scientific knowledge, fulfilling a duty to society and helping to establish a professional reputation [Besley, Newman et al, 2020]. Similarly, in a study by Davies [2021], scientists indicated six clusters of potential roles that science communication plays in society, which were the value of accountability, i.e.…”
Section: Type Of Contributionmentioning
confidence: 99%
“…More extended accounts are given elsewhere in science communication literature. In the context of teaching and training, a number of articles have either framed how science communication's societal goals should be taught (Baram-Tsabari & Lewenstein, 2017a, 2017bMercer-Mapstone & Kuchel, 2017;Seethaler et al, 2019) or investigated how, in practice, such teaching is carried out (Besley et al, 2016;Besley & Tanner, 2011;Bray et al, 2012;Yeoman et al, 2011). While these accounts mobilize different languages for discussing the aims of science communication, and often focus on skills connected to content production rather than on reflection about the effects of communication, they incorporate teaching goals such as encouraging reflection "on science and science communication's role within society; on processes, concepts, and institutions of science communication; and on [participants'] own process[es] of learning about and doing science communication" (Baram-Tsabari & Lewenstein, 2017b, p. 294) and thus suggest that an integral part of becoming adept in science communication is the ability to reflect on its role in society.…”
Section: The Role and Value Of Science Communication In Societymentioning
confidence: 99%
“…While these accounts mobilize different languages for discussing the aims of science communication, and often focus on skills connected to content production rather than on reflection about the effects of communication, they incorporate teaching goals such as encouraging reflection “on science and science communication’s role within society; on processes, concepts, and institutions of science communication; and on [participants’] own process[es] of learning about and doing science communication” (Baram-Tsabari & Lewenstein, 2017b, p. 294) and thus suggest that an integral part of becoming adept in science communication is the ability to reflect on its role in society. Indeed, one recent study of researchers’ goals for their science communication activities (Besley et al, 2020) takes “public-oriented goals” such as “ensuring that our culture values science” and “helping people use science to make better personal decisions” (pp. 3-4) as its key focus.…”
Section: The Role and Value Of Science Communication In Societymentioning
confidence: 99%